BAKTI SOSIAL SEBAGAI UPAYA PENCEGAHAN PENYAKIT TIDAK MENULAR DI BANTENG, YOGYAKARTA - Wiwiek Probowati; Tejo Jayadi; Matahari Bunga Indonesia; Maria Agustina; Bernadeta Amaya Wakitaningtyas (Servirisma, 2024)
Social service activities are held with free health checks such as blood sugar, cholesterol and uric acid. Social service is carried out to assist with initial screening to prevent non-communicable diseases which are the leading cause of death in Indonesia. Activities were carried out in the villages of Banteng, Ngaglik, Sleman, Yogyakarta and residents of the GKJ Dayu congregation. The method of service is to carry out an assessment of the target area and coordinate with GKJ Dayu, the Head of Banteng Village and the formation of a Service Team from the Faculty of Medicine, Duta Wacana Christian University. Evaluation of social service activities is carried out qualitatively by means of discussion and quantitatively by looking at data on participants who registered whether they were successful through screening or not successful through screening. This social service activity was attended by 70 participants who took part in general examinations and were further divided into 5 people undergoing IVA examinations, 5 people undergoing health consultations and 54 people undergoing simple laboratory examinations. From the results of this social service it can be concluded that this activity succeeded in making a real contribution to social service participants who needed free examinations and was able to empower the community by increasing knowledge about non-communicable disease health.